Not only the seed matters: Farmers’ perceptions of sources for banana planting materials in Uganda - Kilwinger, Fleur B.M.; Marimo, Pricilla; Rietveld, Anne M.; Almekinders, Conny J.M.; Dam, Ynte K. van (SAGE Publications, 2020)
The adoption of improved seed and other planting material in developing countries is unsatisfactory, given their potential to increase agricultural productivity. To arrive at a better understanding of the observed adoption rates, it is not only relevant to know which cultivars and variety traits are attractive to farmers: the sourcing planting material by smallholder farmers is often associated in literature with social ties and cultural norms. In this study, means‐end chain analysis was applied to understand farmers’ perceptions on formal and informal sources of banana planting material. The means‐end chain analysis allows respondents to select and verbalize their own constructs to evaluate a product or service. These personally relevant constructs are subsequently linked to their personal goals via laddering interviews. We interviewed 31 Ugandan banana farmers from Western and Central region. Farmers associated formal sources with improved cultivars, tissue culture plantlets and low levels of diversity. Informal seed sources were associated with traditional cultivars, suckers and high levels of diversity. The goals farmers pursued while acquiring planting material, such as financial gains, food security, and to sustain and develop the household, were fairly similar among farmers. Larger, male farmers and Central‐region farmers aimed and preferred to pursue these goals via different means than smaller, female and Western‐region farmers did. These differences among farmers preferences for particular sources indicate that not only cultivar traits should be tailored to farmers’ preferences and needs, but also the characteristics of the sources from which farmers access planting material.